2012
DOI: 10.3109/1061186x.2011.651726
|View full text |Cite
|
Sign up to set email alerts
|

Nano-sized cationic polymeric magnetic liposomes significantly improves drug delivery to the brain in rats

Abstract: In recent years, cationic polymeric magnetic liposomes have shown greater stability and prolonged circulation half-life over traditional liposomes. Here, we examined the capability of cationic polymeric magnetic liposomes in delivering drugs into the brain under magnetic targeting with paclitaxel as the loaded agent. We found that the fabricated paclitaxel-loaded magnetic liposomes had a uniform diameter of 20 nm and were superparamagnetic. After they were injected into rats by the caudal vein, brain paclitaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…However, few studies have investigated brain tissue uptake of liposomes after a short exposure following the intraarterial (IA) injections. Recently Zhao et al reported 15-fold greater uptake of magnetically targeted cationic liposomes after IA injection, compared to intravenous injection [3]. We also observed similar advantages of cationic liposomal preparations during IA injection particularly when injected during transient cerebral hypoperfusion (TCH).…”
Section: Introductionsupporting
confidence: 80%
“…However, few studies have investigated brain tissue uptake of liposomes after a short exposure following the intraarterial (IA) injections. Recently Zhao et al reported 15-fold greater uptake of magnetically targeted cationic liposomes after IA injection, compared to intravenous injection [3]. We also observed similar advantages of cationic liposomal preparations during IA injection particularly when injected during transient cerebral hypoperfusion (TCH).…”
Section: Introductionsupporting
confidence: 80%
“…Several nanosynthetic compounds have been designed to effectively deliver drugs to the brain. 119,120 Similarly, phtobioactive nanoliposomes, such as Orthosiphon stamineus extract nanoliposomes, have higher bioavailability and in vitro antioxidant activity. 121 Curcumin encapsulated nanoliposomes show higher bioavailability after oral treatment in rats with enhanced antioxidant activity.…”
Section: 109mentioning
confidence: 99%
“…Naked SPIONs are also able to passage brain endothelial cells in culture subjected to an external magnetic field [8]. Interestingly, many studies show the advantages of incorporating SPIONs into liposomes thus forming magneto-liposomes that are magnetic responsive [12,24,25,[65][66][67]. Liposomes denote a group of well-established drug carriers for drug delivery purposes.…”
Section: Magnetic Nanoparticles Can Be Encapsulated In Liposomesmentioning
confidence: 99%